Grammatical Tone Pattern in Ùhànmì - Rokeeb Tunde Afeez; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
This study explores the grammatical tone pattern in Ùhànmì, a speech form that belongs to a sub-group of Edoid language family spoken in Ìṣùà-Àkókó of Òǹdó State, Nigeria. The study employs qualitative research method. Data collection was carried out using Ibadan 400 word- list, and was also modified to include sentences in the speech form. The data was sourced from native speakers of the language whose ages range between 50 and 70. The informants were asked questions and their responses in the speech form were recorded, translated and transcribed for accuracy. The study adopts the framework of autosegmental-phonology for its analysis. In the study, specific areas are examined with a view to shed light on the tone system of the speech form. The areas that are investigated include the basic tones in the speech form, functions of tone, and tonal processes in the speech form. Findings from the study demonstrate that Ùhànmì operates four basic tone levels; these are high, mid, low and falling tones. Tone is a unique feature in Ùhànmì, quite distinct from segmental feature. The study reveals that these tones distinguish meaning of segmentally identical words. The study also shows that tones play a distinctive grammatical function in present and past tense. Tonal processes such as tone simplification, tone raising, tone elision, and tone polarization are observed in the speech form. The research is motivated by the need to prevent the speech form from extinction. The study also stems from the missing gap in the knowledge as there is a paucity of publication on the speech form. The research contributes to knowledge in the field of phonology.